Characterization of an adduct between CC-1065 and a defined oligodeoxynucleotide duplex. - Needham-VanDevanter, D R (1984)
CC-1065 is a potent antitumor antibiotic produced by Streptomyces zelensis. The drug binds covalently through N-3 of adenine and lies within the minor groove of DNA. Previous studies indicated that CC-1065 reacted with adenine in DNA to yield a thermally labile product that could be used to reveal its sequence specificity. These studies also provided insight into a DNA sequence (5'-CGGAGTTAGGGGCG-3') which should bind one molecule of CC-1065 in an unambiguous manner. This sequence, which contains the CC-1065 adenine binding site within the sequence 5'-TTA-3' was chemically synthesized together with the complementary strand. CC-1065 reacted with the oligoduplex to give an adduct that maintained the B-DNA form and had a final CD spectrum similar to those of the CC-1065 complexes formed with calf thymus DNA. The above 14mer was 5' end-labelled with 32P, annealed with its complementary strand, reacted with CC-1065 and heated. Drug-mediated strand breakage was evaluated on a sequencing gel. A single break occurred in the labelled strands to give a fragment that migrated as an 8.5mer; subsequent piperidine treatment produced a fragment that migrated as a 7mer, which is the size expected from the known binding of CC-1065 at adenine in 5'-TTA-3' sequences.